Character Formation in Islamic Boarding Schools: The Internalization of Spiritual Values - Nur Khasanah; Lely Ferdiagustina; Dita Fitri Ardianti; Nur Laili Zakiyah Mughniyah; Beny Sintasari (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
The decline of morality and adolescent self-control in the digital era poses critical challenges for Islamic educational institutions internalizing religious character values. This study analyzes the strategies, supporting factors, and obstacles in internalizing spiritual values through habituation methods at MA Al-Urwatul Wutsqo Jombang. Using a qualitative case study approach, this three-month field research collected primary data through in-depth interviews with six key informants, including school leaders, two Islamic Education teachers, and a student representative, combined with observation and documentary study. Data were analyzed using the Miles, Huberman, and Saldana interactive model, with trustworthiness verified through triangulation. Findings show that spiritual value internalization is systematically driven by an integrated pesantren-based curriculum governing habituation of obligatory and sunnah prayers and Al-Qur'an literacy standards. Active teacher involvement as behavioral role models accelerates the transformation of moral knowing into moral action. Despite discipline obstacles, restorative religious and academic sanctions reduce students' resistance. The study concludes that the dialectic between strong institutional regulation and exemplary teacher behavior (uswah hasanah) transforms external control into self-control, offering an integrated character management model for formal educational institutions.